2014
DOI: 10.1172/jci65178
|View full text |Cite
|
Sign up to set email alerts
|

RIP140 increases APC expression and controls intestinal homeostasis and tumorigenesis

Abstract: Deregulation of the Wnt/APC/β-catenin signaling pathway is an important consequence of tumor suppressor APC dysfunction. Genetic and molecular data have established that disruption of this pathway contributes to the development of colorectal cancer. Here, we demonstrate that the transcriptional coregulator RIP140 regulates intestinal homeostasis and tumorigenesis. Using Rip140-null mice and mice overexpressing human RIP140, we found that RIP140 inhibited intestinal epithelial cell proliferation and apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 48 publications
7
76
0
Order By: Relevance
“…RIP140 might be an attractive target to sensitize tumor cells to retinoid-based differentiation therapy in the cancer stem cell model [35]. Moreover, RIP140 was reported to control the intestinal homeostasis and tumorigenesis through upregulation of APC [36], a negative regulator of Wnt/beta-catenin signaling, which was very consistent with our observation in this study though RIP140 negatively regulated beta-catenin/TCF signaling in colon cancer and HCC through different mechanism. These studies suggested that RIP140 might regulate the activity of beta-catenin/TCF signaling at different levels.…”
Section: Discussionsupporting
confidence: 88%
“…RIP140 might be an attractive target to sensitize tumor cells to retinoid-based differentiation therapy in the cancer stem cell model [35]. Moreover, RIP140 was reported to control the intestinal homeostasis and tumorigenesis through upregulation of APC [36], a negative regulator of Wnt/beta-catenin signaling, which was very consistent with our observation in this study though RIP140 negatively regulated beta-catenin/TCF signaling in colon cancer and HCC through different mechanism. These studies suggested that RIP140 might regulate the activity of beta-catenin/TCF signaling at different levels.…”
Section: Discussionsupporting
confidence: 88%
“…The Wnt pathway involves various feedback loops that balance the opposing processes of cell proliferation and differentiation. Studies indicate that, even in the presence of heterozygousactivating mutations downstream of the FRZ receptor, mutationdriven Wnt-signaling activation can be further enhanced in APC min/+ mice and cells (40)(41)(42)(43)(44)(45). Our results highlighted that SETD2 fine-tuned Wnt signaling to safeguard ISCs or progenitor cells in the intestine, whereas downregulation facilitated inherently more proliferative and progenitor traits in ISCs in the Apc-mutated background ( Figure 8E).…”
Section: Methodsmentioning
confidence: 71%
“…RIP140 could implicate in the control of energy expenditure, metabolism, cognition, mammary gland development, and intestinal homeostasis [21,22]. Furthermore, RIP140 was also involved in Fig.…”
Section: Discussionmentioning
confidence: 99%